Testing Job Satisfaction as a Mediator Between Managers 'Charismatic Leadership and Followers' Affective Organizational Commitment - Ozgul, Burcu; Karaca, Dilek; Zehir, Cemal (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2022)
Leadership, affective organizational commitment, and job satisfaction have become important processes among the contemporary human resource functions in today's businesses. This research aims to determine how charismatic leadership of managers affects the level of affective organizational commitment of white-collar employees and whether job satisfaction has any mediation effect in this relationship. Based on this, data were collected through questionnaire method from 417 white-collar employess of 139 small and medium-sized enterprises operating in the manufacturing industry in Istanbul. Hierarchical regression analysis was used to test the hypotheses. According to the results of the research that job satisfaction partially mediates the relationship between the charismatic leadership style of managers and the affective organizational commitment of white collar employees. In the literature, there has been no similar study the mediating role of job satisfaction in the relationship between charismatic leadership style and affective organizational commitment. With this research, various theorical and practical implications are presented.
Keywords: Charismatic Leadership; Affective Organizational Commitment; Job Satisfaction; Social Identity Theory; Social Exchange Theory; Psychological Contract Theory; SOCIAL-EXCHANGE THEORY; TRANSFORMATIONAL LEADERSHIP; NORMATIVE COMMITMENT; CITIZENSHIP BEHAVIOR; ANTECEDENTS; WORK; CONTINUANCE; PERFORMANCE; CONSEQUENCES; METAANALYSIS; Business & Economics